Solar Energy as A Sustainable Alternative Towards Low Carbon Development In Modibbo Adama University Yola - Adeyemi Isiaka, Abdul-Azeez; Aminu Dodo, Yakubu; Dinge Alabura, Ambrose (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
The Stockholm Declaration of 1972 specifically focused on improving the human environment for present and future generations leading to the movement of sustainability in higher education. In recent times, Initiatives to encourage sustainability as a panacea for climate change are being developed through carbon dioxide (CO2) emission reduction by National Governments and University authorities. Research globally led to innovations to promote low-carbon development in universities with varying best practices. This study aims to assess carbon emissions from annual electric energy consumption to reduce the University’s contribution to global warming. The paper presents a case study of energy consumption at Modibbo Adama University (MAU) and analyzes the extent, sources, and quantities of emissions from electricity use towards reducing universities’ contribution to global warming. Using annual data of electricity from metered sources to determine the extent of carbon emission, the study showed an average annual electricity consumption of about 1703632 (kWh), estimated to be about 747894.45 kgCO2 (748MtCO2) of carbon emissions. By introducing solar energy sources through PV installations in selected service sectors, a study reveals a 71% reduction in carbon emissions in the Academic Areas. In comparison, the replacement of electricity with solar energy in Students’ Hostels and Commercial Centers shows a 15% and 9% reduction in carbon emission respectively and about 5% carbon emission reduction in the Staff Quarters. Finally, integrating fossil-fuel-powered energy sources with renewable/solar energy and promoting training, intensifying research development in solar energy technology as well as granting sufficient financial incentives to encourage local producers of solar energy systems would stimulate low-carbon development in the university.